Malinowski's formative contribution to American folklore studies - Korom, Frank J. (Svetovi (Ljubljana), 2024)
Bronisław Malinowski (1884-1942) was a foundational force in the development of function-alist theory in the discipline of anthropology. Based on intensive fieldwork in the Trobriand Islands, his pragmatic theory stimulated much discussion and debate in anthropological circles. Lesser known, however, is the influence that Malinowski had on the development of modern performance studies in the United States among folklore scholars. This research note focuses on Malinowski’s writings concerning the language of myth and magic, since these were the aspects of his work that appealed most to American scholars of performance in the 1970s.
Keywords: antropologija religije; besedilo; context; eng; ethnography; filozofija; folkloristics; folkloristika; jezik; kontekst; language; magic; magija; Malinowski, Bronisław; mit; myth; performance; performans; philosophy; slv; sociolinguistics; sociolingvistika; text